The Effect of Yoga on Back Pain, Anxiety and Sleep Quality of Pregnant Women: A Systematic Literature Review - Setyowati, Eka; Widyawati, Melyana Nurul; Pramana, Cipta (Indonesian Journal of Global Health Research, 2025)
Pregnant women often experience various physical and psychological discomforts, such as back pain, anxiety, and sleep disorders that adversely affect maternal and fetal health. One approach that has to widely studied is yoga, which is believed to be able to reduce discomfort.Objective: To analyze and evaluate the literature regarding the effects of yoga on back pain, anxiety and sleep quality in pregnant women.Methods: This study used the Systematic Literature Review (SLR) method with the PRISMA approach. The articles analyzed were obtained from the Google Scholar, PubMed, and ResearchGate databases with the keywords "pregnancy, yoga, anxiety, low back pain, and sleep quality." Inclusion criteria used the PICOS framework and resulted in 15 relevant articles.Results: An analysis of 15 articles showed that yoga is consistently effective in reducing back pain, reducing anxiety, and improving sleep quality in pregnant women, especially in the second and third trimesters.Conclusion: Yoga is a safe and effective intervention for pregnant women to reduce back pain, reduce anxiety and improve sleep quality so it can be used as an alternative to improve the overall well-being of pregnant women.